Statehood and governance: challenges in Southeast Asia - Jörg Faust; Aurel Croissant (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
While the emerging democracies of Southeast Asia still are characterised by legitimacy crises or have already collapsed, a higher level of political stability persists in most of the region's autocracies. In most countries of South-East Asia, however, the state's monopoly on the legitimate use of force is only partially enforced. In most of the region's countries the potential for further socioeconomic development is seriously constrained by the tight, uncontrolled and opaque nexus of political and economic elites. Yet, given the strategic importance of South-East Asia and the heterogeneity of foreign policy interests of significant third countries, it seems unrealistic in the short to medium term, to expect that development policy could make a structural contribution to the establishment or consolidation of liberal democracy in the region.
Keywords: 330